A systematic review of economic evaluations of whole-genome sequencing for the surveillance of bacterial pathogens. Issue 2 (15th February 2023) - Price, Vivien; Ngwira, Lucky Gift; Lewis, Joseph M.; Baker, Kate S.; Peacock, Sharon J.; Jauneikaite, Elita; Feasey, Nicholas
Abstract : Whole-genome sequencing (WGS) has unparalleled ability to distinguish between bacteria, with many public health applications. The generation and analysis of WGS data require significant financial investment. We describe a systematic review summarizing economic analyses of genomic surveillance of bacterial pathogens, reviewing the evidence for economic viability. The protocol was registered on PROSPERO (CRD42021289030). Six databases were searched on 8 November 2021 using terms related to 'WGS', 'population surveillance' and 'economic analysis'. Quality was assessed with the Drummond–Jefferson checklist. Following data extraction, a narrative synthesis approach was taken. Six hundred and eighty-one articles were identified, of which 49 proceeded to full-text screening, with 9 selected for inclusion. All had been published since 2019. Heterogeneity was high. Five studies assessed WGS for hospital surveillance and four analysed foodborne pathogens. Four were cost–benefit analyses, one was a cost–utility analysis, one was a cost-effectiveness analysis, one was a combined cost-effectiveness and cost–utility analysis, one combined cost-effectiveness and cost–benefit analyses and one was a partial analysis. All studies supported the use of WGS as a surveillance tool on economic grounds. The available evidence supports the use of WGS for pathogen surveillance but is limited by marked heterogeneity. Further work should include analysis relevant to low- and middle-income countries and should use real-world effectiveness data.